The protective impact of betaine on the tissue structure and renal function in isoproterenol‐induced myocardial infarction in rat - Ghartavol, Mohammad Maram (Mol Genet Genomic Med, 2019)
BACKGROUND: Myocardial infarction is one of the most common life threatening diseases that may lead to renal disorders via oxidative stress and inflammation. Betaine is a safe and well‐tolerated compound exhibiting beneficial antioxidant and anti‐inflammatory properties. Previous studies have demonstrated protective effects of betaine against myocardial infarction and renal injury. This study aimed to investigate the protective effect of betaine on tissue structure and renal function after isoprenaline‐induced myocardial infarction in rats. METHODS: Fifty Wistar strain male albino rats, weighing 200 ± 10, were selected for the study. The animals were housed individually under standard environmental conditions (Light–dark cycle, temperature and constant humidity) for 1 week. After acclimatization, they were randomly divided into five groups. G1, G2, and G3 groups received betaine at doses of 50, 150, and 250 mg/kg body weight/day via gavage for a period of 60 days. After 60 days, isoprenaline is injected subcutaneously (200 mg/kg body weight). In the isoprenaline group (G4), the rats were injected with isoprenaline (200 mg/kg body weight) and the control group (G5) received a standard diet (Without isoprenaline). Then, isoproterenol solution was used for induction of myocardial infarction. At the end, the expression of nitric oxide synthase (iNOS) protein was detected using immunohistochemical analysis and kidney tissues were assessed via histopathological analysis. In addition, serum level of TNF‐α and creatinine level were measured via ELISA test and colorimetric methods, respectively. RESULTS: The results of our study indicate that isoproterenol‐induced renal histopathological injury without changing creatinine level. Betaine has protective effects against renal injuries induced by isoprenaline and the expression of nitric oxide synthase (nNOS) protein showed no significant difference in all groups. Further, betaine reduced TNF‐α level significantly. CONCLUSION: According to our results, betaine has protective effects on isoprenaline‐induced renal failure via a decrease in TNF‐α level and nitric oxide synthase.